PERILAKU PETANI PASCA PENERAPAN SYSTEM OF RICE INTENSIFICATION (SRI) DI KABUPATEN ACEH BARAT - Haswinda Hasbi; Fajri .; Indra . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
This study aims to analyze the influence of socio-economic characteristics of  the farmers (Age, education, number of dependents, duration of business and income) To the behavior of farmers after the application of SRI (System of Rice Intensification), to know the size of farmer probability after SRI method implementation to stop or continue SRI method in Kaway XVI sub-district inWest Aceh regency, And to know the strategic steps undertaken so that the application of SRI method will be increasing.The research  location in Kaway XVI sub-district which is one center of rice production and also become one of SRI pilot location in WestAcehregency  with sample number 55 respondent.Data analysis used is logistic regression, Odds Ratio, SWOT, and QSPM. The results of this study indicate age, education, number of dependents, length of farming and income affects the behavior of farmers after the implementation of SRI. Probability of farmers after implementation of SRI method which continued the application of SRI method as much as 20 people or 36,36% from total respondents, while farmer who did not continue the application of SRI method counted 35 people or 63,64% from total respondent